The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.24191/e-aj.v10i1.13353
|View full text |Cite
|
Sign up to set email alerts
|

The Concept and Application of ICT on SMEs performance in Nigeria: Limitation and Challenges

Abstract: Small and Medium Enterprises (SMEs) play a vital role in growing and building developing nations' national economy. This study investigates a deep understanding of the influence of Information Communication Technology (ICT) on SMEs' performance in Nigeria. The study found out that most SME owners engage in local business practices in nature of the operation, and marketing strategies are limited within the country. Hence, this is a growing concern, the need to broaden the field of doing business through global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For instance, a study on digital infrastructure and the performance of MSMEs carried out by Cueto et al (2022) and Kawira (2021); established that social media platforms, the internet, and mobile phones increased the performance of the MSMEs. In contrast, Onileowo and Fasiku (2021) found that communication technologies had an insignificant effect on performance.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…For instance, a study on digital infrastructure and the performance of MSMEs carried out by Cueto et al (2022) and Kawira (2021); established that social media platforms, the internet, and mobile phones increased the performance of the MSMEs. In contrast, Onileowo and Fasiku (2021) found that communication technologies had an insignificant effect on performance.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, investments in digital infrastructures promote improved performance of MSMEs. This argument is potentially linked to many propositions by Cueto et al (2022) and Onileowo and Fasiku (2021). The adoption of ICT has the potential to improve the performance of MSMEs, but more efforts should be made to reduce the limitations and challenges associated with ICT adoption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations